A Systematic Review of Synthetic and Anticancer and Antimicrobial Activity of Quinazoline/Quinazolin‐4‐one Analogues - Neha Manhas; Gobind Kumar; Sanjeev Dhawan; Talent Makhanya; Parvesh Singh (ChemistryOpen, 2025)
Abstract Quinazolines/quinazolin‐4‐ones are significant nitrogen‐containing heterocycles that exist in various natural products and synthetic scaffolds with diverse medicinal and pharmacological applications. Researchers across the globe have explored numerous synthetic strategies to develop safer and more potent quinazoline/quinazolinone analogues, particularly for combating cancer and microbial infections. This review systematically examines scholarly efforts toward understanding this scaffold's synthetic pathways and medicinal relevance, emphasizing the role of metal and non‐metal catalysts and other reagents in their synthesis. Additionally, the article discusses selected compounds’ anticancer and antimicrobial properties, with a brief look into their structure‐activity relationships.